UNSTEADY MHD COUETTE FLOW BETWEEN TWO PARALLEL HORIZONTAL POROUS PLATES IN AN INCLINED MAGNETIC FIELD (FULafia Journal of Science and Technology, 2019)
In this paper, the study of unsteady Magnetohydrodynamic (MHD) couette flow between two parallel horizontal porous plates in an inclined magnetic field was carried out. The momentum and energy equations are written in a dimensionless form using the  imensionless parameters. Variable separable technique was employed to solve the velocity profile and temperature distribution. However, out of many results, we conclude that, at high Hartmann number Ha, the velocity u of the fluid decreases. When the magnetic field is high, it reduces the energy loss through the plates.
Keywords: Couette Flow; Porous Plates; Magnetic Field; Hartmann Number; Grashof Number; Prandit Number